Biomas Energy Potential in Kampar Regency - Kunaifi Kunaifi (UIN Sultan Syarif Kasim Riau, 2012)
Kampar Regency - Riau Province is believed to have large potential for biomass energy, but has not been optimally utilized due to lack of baseline data. This article presents the result of a biomass energy resource assessment in Kampar Regency that used resource-based approach with basic statistical method. The procedure from Biomass Energy Europe was applied to assess the potential of forest biomass, energy crops, agricultural residues and organic wastes. The total theoretical potential of biomass energy in Kampar Regency is 127,635,417.90 GJ/year where 97.933% come from agricultural residues, 2.066% forest biomass and 0.001% organic waste. In this study the agricultural residues also included residues from plantations (oil palm and coconut) and animal residues (cow, buffalo, goat, and poultry). Oil palm contributes to 88.15%, followed by chickens and ducks (5.28%), rice and maize (3.77%), and primary forest residues (2%). The oil palm fronds are the largest contributor i.e. 58.8% of the total oil palm potential and 51.8% of the total biomass energy potential in Kampar Regency.Keywords – biomass, energy, Kampar, potential, Statistics.